Empowering strategies, leader behavior and interventions - Jeyavelu, S. (2003)
Organizations increasingly resort to creating an empowered work force to become effective, innovative, reduce costs, and improve quality of products and services to tackle competition. This paper extends conceptualization of empowerment defined as enhanced feeling of self-efficacy to organizational interventions, leader behavior and reattribution training. The paper looks into the relationship between empowerment and performance; the various terms of self-efficacy beliefs; self-efficacy in the organizational context; organizational contextual factors that affect empowerment and organizational intervention strategies; empowering leadership; and reattribution training as an intervention tool to empower employees. - Reproduced.
Keywords: Leadership; Organizational behaviour; Workers participation